Pengukuran Keakuratan Metode K-Means untuk Menentukan Status Gizi Balita - Adimas Ketut Nalendra (Politeknik Sawunggalih Aji, 2018)
Infancy is an optimal growth and development that occurs at the age of 0 to 2 years. According to The Guverment's Basic Health Research shows that the number of children under five in Indonesia with malnutrition in 2013 reached 28.1 percent of the population. To analyze malnutrition can use the K-Means method with a variable weight and height. For verification, the Growth Chart table is used to measure the accuracy of the K-Means method. Research uses the CRIPS-DM cycle model that is used to handle a data mining project. From the results of the test, the accuracy rate is 34%. Using the K-Means method still has a small level of accuracy so that other methods are needed that have higher accuracy.